Attitudes, Perceptions of Ability, Barriers, and Expectations of Lecturers in the Use of ICT in Online English Learning - Apriani, Eka; Arsyad , Safnil; Syafryadin, Syafryadin; Baihaqi, Yasmika; Wijayanti, Erfin; Esmianti, Farida; Supardan, Dadan (UNIB Press, 2025)
This study aims to analyze the attitudes, perceptions of abilities, barriers, and expectations of IAIN Indonesia lecturers in the use of ICT in online English learning. The research method uses